Motivasi Konsumsi Kolaboratif dalam Era Ekonomi Berbagi - Fadillah, Fadillah Wahyu Saputri; Mayasari, Iin (Jurnal Manajemen dan Bisnis Madani, 2024)
Abstract This study analyzes the motivational factors in collaborative consumption in the sharing economy era, focusing on economic aspects, social orientation, ecological aspects, and personal values that influence individual participation. The analysis shows the dominant role of economic factors in participation motivation, with differences between service providers and users. Social motives and environmental concerns also have a big influence on consumption behavior. This research was conducted through 60-minute interviews with five informants, highlighting experienced consumers on online platforms such as Airbnb, Go-Jek, Grab, OLX, and Bukalapak. The data provides insight into the motivations behind changing consumption patterns. Analysis includes economic aspects, utility, social orientation, emotional, environmental, and personal values. Keywords: Collaborative consumption, motivation factors, economic aspects